The Effect of the Individualized Education Program on Early Reading Ability for Special Needs Students Based on Reading Interest in Inclusive Elementary Schools - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari; Trisnani, Rischa Pramudia (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
This study aims to examine the effect of the Individualized Education Program (IEP) on early reading ability of students with special needs in Inclusive Elementary Schools in Magetan Regency based on reading interest. This study used 2 x 2 factorial design with pre-test and post-test control group design. The samples were selected using a cluster random sampling technique; 35 students were selected as experimental group members, while 37 were selected as control group members. Reading interest scale was used to measure the reading interest of students, and early reading ability was measured using early reading ability test. Two-way ANOVA was used to analyse the hypothesis. The test was performed with a multiple comparison test using Scheffe's method. The results show that (1) there are differences in the early reading ability of students with special needs who are taught by applying the IEP and those who are not; (2) there are differences in the early reading ability of students with special needs between groups of students with high reading interest and low reading interest; (3) there is an interaction between the application of IEP and reading interest in improving the early reading ability of students with special needs.